Towards international cultural diversity management of public relations: viewpoints of chairmen/CEOs - Abdullah, Zulhamri (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
This paper aims to promote a better understanding of how cultural diversity is practised in multinational corporations in Malaysia. Cultural diversity considers a complex element of management facets within the corporate culture. Managing cultural diversity requires a holistic approach especially from top management personnel in terms of cultural sensitivity and ‘local focused’. A qualitative research method, in-depth interviews was employed. The findings revealed that localisation is a hallmark of Asian strategy in winning competitive advantages in the global marketplace. All management personnel stressed the importance of cultural sensitivity in practising business strategy in multinational corporations. Surprisingly, cultural diversity is not a barrier to the management of business strategy, instead it is seen as huge opportunities for Malaysian corporations to create their own corporate identity to compete with global competitors.